Allogeneic blood transfusions and infection risk in lumbar spine surgery: An American College of Surgeons National Surgery Quality Improvement Program Study. Issue 5 (26th March 2022) - Falsetto, Amedeo; Roffey, Darren M.; Jabri, Hussam; Kingwell, Stephen P.; Stratton, Alexandra; Phan, Philippe; Wai, Eugene K.
Abstract: Background: Allogenic blood transfusions can lead to immunomodulation. Our purpose was to investigate whether perioperative transfusions were associated with postoperative infections and any other adverse events (AEs), after adjusting for potential confounding factors, following common elective lumbar spinal surgery procedures. Study design and methods: We performed a multivariate, propensity‐score matched, regression‐adjusted retrospective analysis of the American College of Surgeons National Surgical Quality Improvement Program database between 2012 and 2016. All lumbar spinal surgery procedures were identified ( n = 174, 891). A transfusion group (perioperative transfusion within 72 h before, during, or after principal surgery; n = 1992) and a control group (no transfusion; n = 1992) were formed. Following adjustment for between‐group baseline features, adjusted odds ratios (aOR) and 95% confidence intervals (95% CI) were calculated using a multivariate logistic regression model for any surgical site infection (SSI), superficial SSI, deep SSI, wound dehiscence, pneumonia, urinary tract infection, sepsis, any infection, mortality, and any AEs. Results: Transfusion was associated with an increased risk of each specific infection, mortality, and any AEs. Statistically significant between‐group differences were demonstrated with respect to any SSI (aOR: 1.48; 95% CI: 1.01–2.16), deep SSI (aOR: 1.66; 95% CI: 0.98–2.85), sepsis (aOR: 2.69; 95% CI: 1.43–5.03), wound dehiscence (aOR: 2.27; 95% CI: 0.86–6.01), any infection (aOR: 1.46; 95% CI: 1.13–1.88), any AEs (aOR: 1.80; 95% CI: 1.48–2.18), and mortality (aOR: 2.17; 95% CI: 0.77–6.36). Conclusion: We showed an association between transfusion and infection in lumbar spine surgery after adjustment for various applicable covariates. Sepsis had the highest association with transfusion. Our results reinforce a growing trend toward minimizing perioperative transfusions, which may lead to reduced infections following lumbar spine surgery.